Parametric shape modification and application in a morphological biomimetic design. Issue 1 (January 2015) - Kim, Sun-Joong; Lee, Ji-Hyun
Abstract Biomimetic design performed to develop a solution-shape has been offered as a successful approach for overcoming the limitations of typical design methods. Especially for the nose-shape of high-speed trains, the morphological characteristics of a superior bio-model were used in the design process. However, current design methods using the biomimetic approach, particularly in the morphological domain, do not support a technique to evaluate how close the new solution is to the optimal one; nor do they support alternative methodologies used to validate and verify the solution-shape being developed. Solution optimization in a biomimetic design means not only preserving the original shape of a bio-model but also validating and verifying it. Shape optimization for a design problem should accompany shape evaluation and modification conducted according to criteria involving both evolutionary traits and technological constraints. In this research we suggest a method to verify the original shape, and to validate the solution, using theoretical backgrounds from both systematic biology and evolutionary biology. In this paper, the morphological characteristics of a bio-model are verified and modified using a quantitative method. To validate the solution developed, new criteria are applied for high-speed-train design.